2003
DOI: 10.1097/00002820-200312000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Symptom Distress, Catastrophic Thinking, and Hope in Nasopharyngeal Carcinoma Patients

Abstract: The purposes of this study were to explore symptom distress, catastrophic thinking (catastrophizing) and hope, and factors predicting hope in Taiwanese nasopharyngeal carcinoma (NPC) patients within 3 years of receiving radiation therapy (RT). Instruments used were the modified Symptom Distress Scale, disease catastrophizing scale (modified from Coping Strategies Questionnaire), and Herth's Hope Index. Adult NPC patients (N = 115; 33 undergoing RT, 44 who completed RT within 1 year, and 38 who completed RT mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 33 publications
2
56
0
Order By: Relevance
“…The mean hope level found in this study's patient population was in the upper range but comparable to those found in other studies with HHI scores ranging between 32.5 and 39. [17][18][19][20][34][35][36] The average pain score in the study population was also well within the range found in other related studies. 17,21,34,35 Our results expand on the existing research in this field by incorporating additional psychospiritual factors into the assessment of the relationship between pain and hope.…”
Section: Discussionsupporting
confidence: 87%
“…The mean hope level found in this study's patient population was in the upper range but comparable to those found in other studies with HHI scores ranging between 32.5 and 39. [17][18][19][20][34][35][36] The average pain score in the study population was also well within the range found in other related studies. 17,21,34,35 Our results expand on the existing research in this field by incorporating additional psychospiritual factors into the assessment of the relationship between pain and hope.…”
Section: Discussionsupporting
confidence: 87%
“…Pain catastrophizing refers to the tendency to ruminate upon and magnify the threat value of pain sensations. Cancer patients who engage in pain catastrophizing not only report higher levels of pain, but also experience much higher levels of anxiety and interference with daily activities due to pain [8,9]. Third, recent evidence suggests that cancer patients who hold back on sharing their concerns about pain or who are unwilling to express emotions related to the cancer experience are more likely to experience high levels of pain and lower quality of life [10].…”
Section: Conceptual Backgroundmentioning
confidence: 99%
“…However, test-retest reliability was not examined due to logistical concerns in readministering the test to hospice cancer patients. Construct validity was tested by five theoretically or empirically related assumptions: (1) higher levels of pain severity (measured by the MPI-sC Pain Severity subscale and four items in BPI-Pain intensity subscale) are related to increased affective distress (assessed by the MPI-sC Affective Distress subscale), mood disturbance (measured by the Hospital Anxiety and Depression Scale [HADS], one of the most frequently used depression and anxiety scales in cancer pain populations) [3,5,32,36], and decreased sense of control in life because of pain (measured by the MPI-sC Life Control subscale); (2) higher levels of pain intensity are related to increased pain interference with activities (assessed by the MPI-sC Pain Interference subscale and the Karnofsky Performance Scale [KPS]) [15]; (3) higher levels of pain interference with activities are related to affective distress (assessed by the MPI-sC Affective Distress subscale and HADS subscales); (4) higher levels of Pain Interference are related to lower Life Control because of pain (both assessed by MPI-sC subscales); and (5) higher levels of pain-related Affective Distress are related to lower levels of Life Control because of pain [10,11,17,18,20,21,27,33,35].…”
Section: Designmentioning
confidence: 99%
“…Thus, the construct validity of the MPI-sC was examined by comparing its scores to those of four instruments: (1) the MPI-screening (Chinese) [16,34] (2) the HADS [36], (3) four pain-intensity measures from the BPI-short form (worst pain, least pain, pain on average, and pain now) [11,18], and (4) the KPS [15]. All these instruments have been translated into Chinese.…”
Section: Instrumentsmentioning
confidence: 99%
See 1 more Smart Citation